2022
DOI: 10.1038/s41598-022-14788-5
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapy of pyrrolo[2,3-d]pyrimidine antifolates in a syngeneic mouse model of high grade serous ovarian cancer and the impact on the tumor microenvironment

Abstract: Novel therapies are urgently needed for epithelial ovarian cancer (EOC), the most lethal gynecologic malignancy. In addition, therapies that target unique vulnerabilities in the tumor microenvironment (TME) of EOC have largely been unrealized. One strategy to achieve selective drug delivery for EOC therapy involves use of targeted antifolates via their uptake by folate receptor (FR) proteins, resulting in inhibition of essential one-carbon (C1) metabolic pathways. FRα is highly expressed in EOCs, along with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…The mitochondrial matrix has an alkaline pH (pH 7.7−7.9) 49,50 compared to the cytosol (pH 7.0−7.4); 50,51 for docking studies, the protein and our proposed ligands were prepared accordingly. From the docking studies, the 5-atom-bridged compounds showed preferential binding (−13.3 kcal/mol for 11, −10.2 kcal/mol for 9, and −10.0 kcal/mol for 3) and the 3-to 4-atombridged compounds (1,2,4,12,13,14,15,16) showed slightly decreased docked scores (∼−9 kcal/mol). Analogues with heteroatoms in the bridge (5−8) were found to have poorer docked scores (−7.5 to −8.6 kcal/mol).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mitochondrial matrix has an alkaline pH (pH 7.7−7.9) 49,50 compared to the cytosol (pH 7.0−7.4); 50,51 for docking studies, the protein and our proposed ligands were prepared accordingly. From the docking studies, the 5-atom-bridged compounds showed preferential binding (−13.3 kcal/mol for 11, −10.2 kcal/mol for 9, and −10.0 kcal/mol for 3) and the 3-to 4-atombridged compounds (1,2,4,12,13,14,15,16) showed slightly decreased docked scores (∼−9 kcal/mol). Analogues with heteroatoms in the bridge (5−8) were found to have poorer docked scores (−7.5 to −8.6 kcal/mol).…”
Section: ■ Introductionmentioning
confidence: 99%
“…RFC is ubiquitously expressed in normal and malignant cells in humans and is the major tissue folate transporter . PCFT is the principal transporter of folates in the upper gastrointestinal tract but shows a more limited tissue distribution than RFC. PCFT is widely expressed in human tumors and is active under acidic conditions characterizing the tumor microenvironment. , FRα is expressed in normal epithelial tissues (e.g., mammary ducts, lungs, kidneys, choroid plexus) and a wide range of tumors (e.g., breast, cervical, renal, ovarian, endometrial cancers); FRβ is expressed in hematopoietic tissues, activated myeloid cells, and tumor-associated macrophages (TAMs). , …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, for several series, these effects on FR-targeted cell inhibitions were more pronounced for FRβ and were independent of the nature of the aromatic side chain. This suggests a potential utility of these compounds for selectively targeting FRβ-expressing cells including protumor TAMs in the tumor microenvironment. , …”
Section: Discussionmentioning
confidence: 99%
“…This suggests a potential utility of these compounds for selectively targeting FRβ-expressing cells including protumor TAMs in the tumor microenvironment. 16,49 By metabolite rescue studies, we identified de novo purine biosynthesis as the targeted pathway for the thieno[2,3d]pyrimidine antifolates and discovered that compounds 1, 2, and 6 also inhibited mitochondrial C1 metabolism. By in vitro assays with monoglutamyl thieno[2,3-d]pyrimidine antifolates and isolated GARFTase and AICARFTase, inhibition of these folate-dependent targets in de novo purine biosynthesis was confirmed.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…According to reports, the cellular uptake of 6-substituted pyrrolo [2,3-d] pyrimidines, depend on multiple (folate) transporters like folate receptor alpha (FRα), FRβ, reduced folate carrier (RFC), and proton coupled folate transporter (PCFT). And they found that the role of folylpolyglutamate synthetase (FPGS) in the retention of 6-substituted pyrrolo [2,3-d] pyrimidines intracellularly ( Dekhne et al, 2020 ; Golani et al, 2020 ; Wallace-Povirk et al, 2021 ; Wallace-Povirk et al, 2022 ). Thus, this hypersensitivity maybe explained by the fact that KB cells express high amount of FRα, which may serve as cellular internalization route for glytrexate.…”
Section: Discussionmentioning
confidence: 99%